Effectiveness of Facebook Remote Live-Streaming-Guided Exercise for Improving the Functional Fitness of Community-Dwelling Older Adults - Chang, Shao-Hsi; Wang, Li-Ting; Chueh, Ting-Yu; Hsueh, Ming-Chun; Hung, Tsung-Min; Wang, Yu-Wen (Frontiers in Medicine, 2021)
Background: The aim of this study was to determine the effect of Facebook remote live-streaming-guided exercise on the functional fitness of community-dwelling older adults. Method: This study used a non-randomized controlled design with single-blinding (outcome assessors). Older adults (mean age = 70.36 ± 4.51 years) were assigned to either the experimental group (n = 39) or the control group (n = 34). The experimental group participated in a 75-minute Facebook remote live-streaming-guided exercise routine twice a week for 8 weeks at home, whereas the control group maintained their original lifestyle without any intervention. Functional fitness was assessed using the Senior Fitness Test, which assessed upper and lower limb flexibility and muscle strength, cardiorespiratory fitness, and balance. The test was administered before and after the intervention. Results: The results revealed that an 8-week Facebook remote live-streaming-guided exercise intervention increased lower limb flexibility and muscle strength and cardiorespiratory fitness in community-dwelling older adults. Conclusion: The current findings suggest that a home-based exercise program using the Facebook platform may be a feasible method to broadly improve the functional fitness of community-dwelling older adults.